2013
DOI: 10.1111/imm.12127
|View full text |Cite
|
Sign up to set email alerts
|

A Thr/Ser dual residue motif in the cytoplasmic tail of human CD1d is important for the down‐regulation of antigen presentation following a herpes simplex virus 1 infection

Abstract: SummaryCD1d-restricted T (natural killer T; NKT) cells are important for controlling herpesvirus infections. Interestingly, herpes simplex virus (HSV) can down-regulate CD1d-mediated activation of NKT cells. We have previously shown that the Thr322 residue in the cytoplasmic tail of human CD1d is important for its intracellular trafficking and functional expression. We proposed that the phosphorylation of T322 is a signal for CD1d lysosomal targeting and subsequent degradation. In the current study, we generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…US3 is one of the early late (␥1) genes expressed during HSV-1 infection, and its expression can be detected at approximately 3 to 4 h postinfection (8,22). Concomitant with US3 expression, the virus rapidly suppresses cell surface expression of CD1d as early as 5 to 6 h postinfection (8,10,13,14). We hypothesized that a rapid shutdown of cytoskeleton-based intracellular vesicular trafficking is a major mechanism of suppression of CD1d expression.…”
Section: Hsv-1 Protein Kinase Us3 Specifically Downregulates the Surfmentioning
confidence: 99%
See 2 more Smart Citations
“…US3 is one of the early late (␥1) genes expressed during HSV-1 infection, and its expression can be detected at approximately 3 to 4 h postinfection (8,22). Concomitant with US3 expression, the virus rapidly suppresses cell surface expression of CD1d as early as 5 to 6 h postinfection (8,10,13,14). We hypothesized that a rapid shutdown of cytoskeleton-based intracellular vesicular trafficking is a major mechanism of suppression of CD1d expression.…”
Section: Hsv-1 Protein Kinase Us3 Specifically Downregulates the Surfmentioning
confidence: 99%
“…We and other groups have demonstrated that HSV-1, upon infection, rapidly and efficiently downregulates a critical antigen-presenting molecule, CD1d, thereby inhibiting the function of NKT cells (8,10,13,14). In addition to downregulating key antigen-presenting molecules such as CD1d and MHC class I/II for the sake of immune evasion (41,42), HSV-1 reprograms the entire cellular machinery for the benefit of its own replication.…”
Section: Hsv-1 and Us3-mediated Cd1d Downregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell culture, constructs, and viral infections HEK293 cells expressing wild-type (WT) CD1d and T322A/S323A mutant have been previously described (25,26). HEK293 cells were kindly provided by Prof. Philip Cohen (MRC Protein Phosphorylation Unit, University of Dundee, Scotland, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the number of NKT cells has recently been correlated with the level of HSV-1-specific antibodies in humans (34). We and others have shown that HSV-1 can inhibit CD1d-mediated antigen presentation to NKT cells by suppressing CD1d recycling (6,25,33,45). This inhibition of NKT cell function by HSV-1 is dependent on cell-to-cell contact of infected APCs and NKT cells, but not due to infection of NKT cells (6).…”
mentioning
confidence: 87%